THERAPEUTIC METHODS USED IN "LITTLE MEDICINE LAW". - F.Ibragimov (Western European Studies, 2025)
This article presents an analysis of the therapeutic methods used in the work of the Minor Canon of Medicine and their effect on the human body. A comparative analysis is made with today's modern medical knowledge
Keywords: Small medical law; therapeutic methods; medicine